KONSTRUKSI POLA GERAK TARI PRAJURITAN DI PAGUYUBAN LESTARI BUDI TAMTAMA SALATIGA - Michael Albert Octavian; S. Sriyadi (Greget: Jurnal Kreativitas dan Studi Tari, 2026)
This study is grounded in the significance of movement pattern construction as a conceptual foundation in creating a coherent and meaningful dance performance. Previous studies on the Prajuritan dance have primarily focused on performance form and socio-cultural values, while analyses of movement pattern construction remain limited. Therefore, this research aims to examine the construction of movement patterns within a choreographic framework in the Prajuritan dance performed by the Lestari Budi Tamtama community, emphasizing formative elements, compositional principles, and structural integration. This study employed a qualitative method with a choreological approach. Data were collected through observations of rehearsals and performances, in-depth interviews, and literature reviews to strengthen the theoretical framework. Data analysis was conducted systematically through data reduction, data presentation, and conclusion drawing. The findings indicate that movement pattern construction is based on the integration of posture and movement elements involving the head, torso, arms, and legs as fundamental structural units. The choreographic structure is developed through motifs, repetition, variation, climax, transition, proportion, logical development, and unity as an integrated compositional framework. Motifs function as the basis for developing movement sequences, while transitions ensure continuity between sections. Repetition and variation enrich movement dynamics, whereas climax serves as the dramatic peak of the performance. Proportion and logical development maintain structural balance and continuity. Overall, these principles create choreographic unity capable of effectively conveying artistic meaning and representing the distinctive character of the dance performance.